Parodies: Creative Materials for Post-pandemic Literary History - Gilbas, Sherill (MASI Mandiri Edukasi, 2024)
Parody is a protected free expression. It is a piece of writing or music that closely mimics the style of a particular author or piece for comedic effect. The main objective of this paper is to present parodies made during the pandemic as aesthetic expression and as literary, educational art as sources of contextual literary history. Specifically, it aimed to identify and analyze the parodies to distinguish the theme, message, and the parody songs’ purpose. The researcher believes this paper may also determine the standard terms related to COVID-19 and the effects of the pandemic on society. This paper employed the qualitative-descriptive type of literary criticism as a research design anchored on the theory of participatory culture. The results of this study identified standard terms used in the pandemic parodies as COVID-19 neologisms. In conclusion, those widely used CoViD-19 terminology could reveal the pandemic's consequences to society. It affected the economy, commerce, education, entertainment, travel, human conduct, and religion. This paper recommends that song parodies be used to teach post-pandemic contexts for historical and literary references.